2014
DOI: 10.1016/j.ijrobp.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Dosimetric Impact of Real-Time Prostate Motion During Volumetric Modulated Arc Therapy

Abstract: Purpose To develop a method for dose reconstruction by incorporating the interplay effect between aperture modulation and target motion, and to assess the dosimetric impact of real-time prostate motion during volumetric modulated arc therapy (VMAT). Methods and Materials Clinical VMAT plans were delivered with the TrueBeam linac for 8 patients with prostate cancer. The real-time target motion during dose delivery was determined based on the 2-dimensional fiducial localization using an onboard electronic port… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 32 publications
(24 reference statements)
2
24
0
Order By: Relevance
“…A simulation study performed using dose reconstruction for conventional and subvolume boost treatments for prostate showed that MLC tracking is effective at mitigating the dosimetric effects of prostate motion and allows for successful GTV and PTV dose delivery (14), as demonstrated in the present study. The dosimetric results for the without-MLC tracking delivery also corresponds closely with other observational prostate dose reconstruction studies (15,16) that have modeled the effect of intrafraction prostate motion on the dose delivery of standard non-MLC tracking treatments. The outlier fractions for which the dose distribution was improved by MLC tracking tended to be lower PTV and CTV doses, lower rectum doses, and higher bladder doses.…”
Section: Discussionsupporting
confidence: 80%
“…A simulation study performed using dose reconstruction for conventional and subvolume boost treatments for prostate showed that MLC tracking is effective at mitigating the dosimetric effects of prostate motion and allows for successful GTV and PTV dose delivery (14), as demonstrated in the present study. The dosimetric results for the without-MLC tracking delivery also corresponds closely with other observational prostate dose reconstruction studies (15,16) that have modeled the effect of intrafraction prostate motion on the dose delivery of standard non-MLC tracking treatments. The outlier fractions for which the dose distribution was improved by MLC tracking tended to be lower PTV and CTV doses, lower rectum doses, and higher bladder doses.…”
Section: Discussionsupporting
confidence: 80%
“…The primary concern is that interplay between tumor motion and beam modulation could result in inadvertent underdosing of the tumor or excessive dose to nearby organs at risk. The interplay effect has been extensively reported on in the setting of IMRT[1417], VMAT[1820], and PBS[21, 22]. These studies then paved the way for the development of mitigation strategies to minimize the potential impact of motion interplay.…”
Section: Motion and Volume Adaptation In Current Radiotherapeutic Parmentioning
confidence: 99%
“…Intrafraction prostate motion is a predominant cause for treatment delivery inaccuracies as multiple studies have shown that the prostate tends to move in an unpredictable way in approximately 50% of all patients with observed motion amplitudes up to 2 cm for certain extreme cases . The dosimetric impact of this residual intrafraction motion is nonnegligible and should be mitigated by accurate monitoring of the prostate position during treatment delivery . To this end, a wide variety of motion monitoring techniques are currently utilized in clinical practice or are under development …”
Section: Introductionmentioning
confidence: 99%